The Impact Of Hepatitis B Knowledge and Stigma on Screening in Canadian Chinese Persons - Dorothy Li; Taryn Tang; Matt Patterson; Michael Ho; Jenny Heathcote; Hemant Shah (Canadian Journal of Gastroenterology)
BACKGROUND: Chronic hepatitis B (CHB) infection is endemic in East Asia, and those who emigrate to North America have higher rates of CHB infection when compared with the general population. To date, Chinese persons residing in Canada have not been mandated to be screened for CHB infection.